High-temperature sequential structural transitions with distinct switchable dielectric behaviors in two organic ionic plastic crystals: [C4H11NBr] [ClO4] and [C4H11NBr] [BF4]. Issue 4 (3rd January 2018) - Lu, Si-Qi; Chen, Xiao-Gang; Gao, Ji-Xing; Lu, Yang; Hua, Xiu-Ni; Liao, Wei-Qiang
Abstract : [C4 H11 NBr] [ClO4 ] and [C4 H11 NBr] [BF4 ] undergo phase transitions from an ordered phase to plastic phase accompanied by switchable dielectric anomalies. Abstract : Two new organic ionic plastic crystals (OIPCs), [TMBM] [ClO4 ] (1 ) and [TMBM] [BF4 ] (2 ) (TMBM = trimethylbromomethyl ammonium), were successfully synthesized. Systematic characterization via differential scanning calorimetry (DSC), variable-temperature single-crystal X-ray diffraction, variable-temperature powder X-ray diffraction (PXRD) and dielectric measurements demonstrated that1 and2 undergo reversible high-temperature sequential phase transitions accompanied by distinct stepwise switchable dielectric anomalies (1 at 358 K and 388 K and2 at 346 K and 379 K). The structural relatively ordered-disordered transitions of ClO4 −, BF4 − and [TMBM] + contributed to the switching of the dielectric constant from the low-dielectric state to the high-dielectric state. Thus, OIPCs consisting of spherical ammonia cations and inorganic acid anions are proven to be promising in the search for high-temperature multi-step switchable dielectric materials.